Genetic diversity and population structure in the US Upland cotton (Gossypium hirsutum L.) - Tyagi, Priyanka; Gore, Michael A; Bowman, Daryl T; Campbell, B. Todd; Udall, Joshua A; Kuraparthy, Vasu (Theoretical and applied genetics, 2014)
KEY MESSAGE : Genetic diversity and population structure in the US Upland cotton was established and core sets of allelic richness were identified for developing association mapping populations in cotton. Elite plant breeding programs could likely benefit from the unexploited standing genetic variation of obsolete cultivars without the yield drag typically associated with wild accessions. A set of 381 accessions comprising 378 Upland (Gossypium hirsutum L.) and 3 G. barbadense L. accessions of the United States cotton belt were genotyped using 120 genome-wide SSR markers to establish the genetic diversity and population structure in tetraploid cotton. These accessions represent more than 100 years of Upland cotton breeding in the United States. Genetic diversity analysis identified a total of 546 alleles across 141 marker loci. Twenty-two percent of the alleles in Upland accessions were unique, specific to a single accession. Population structure analysis revealed extensive admixture and identified five subgroups corresponding to Southeastern, Midsouth, Southwest, and Western zones of cotton growing areas in the United States, with the three accessions of G. barbadense forming a separate cluster. Phylogenetic analysis supported the subgroups identified by STRUCTURE. Average genetic distance between G. hirsutum accessions was 0.195 indicating low levels of genetic diversity in Upland cotton germplasm pool. The results from both population structure and phylogenetic analysis were in agreement with pedigree information, although there were a few exceptions. Further, core sets of different sizes representing different levels of allelic richness in Upland cotton were identified. Establishment of genetic diversity, population structure, and identification of core sets from this study could be useful for genetic and genomic analysis and systematic utilization of the standing genetic variation in Upland cotton.